Strategi Kebijakan Pemberdayaan Perempuan dan Perlindungan Anak di Kabupaten Rembang Tahun 2016 - Alfado Haryadi Saputra; Budi Setiyono; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Strategy of Women’s Empowerment and Child Protection Policy in Rembang Regency 2016 ABSTRACTBacground: The high number of women and children violence, followed by the lack of active PUG institution becomes the the basic reference of researchers to assess the accomplishments of  PUG  implementation in 2016, the efforts of officers in implementing the strategy and the efforts to preserve the mentor category of APE in Rembang.Methods: A qualitative study involves collecting various empirical materials (interviews, personal observations, social interactions) to describe the problem, routine moments and its meaning in individual and social life.Results: The Implementation of policies related to gender mainstreaming in Kabupaten Rembang 2016, in routine evaluation through program evaluation meetings and in the district mid-term district development plan (RPJMD) section has integrated gender issues of strategy and policy direction integration of gender perspective in regional apparatus units.Conclusions: Implementation of gender mainstreaming in Rembang regency 2016, the achievement of the highest appreciation of godsend parahita ekapraya (APE) category of mentor and child-friendly district, while the constraint is limited resources such as supporting gender mainstreaming and technical guidance.Keywords: Strictness, Policy Strategy, Gender Mainstreaming